Customizing mass housing: a dual computer implementation design strategy based on shape grammars - Santos, F. (2019)
This research aims at developing a system for automatic generation of designs that allows housing customers to participate in the design of their house by using mass-customization design. The proposed system is based on shape grammars and will allow future owners to acquire houses that fit their needs while simultaneously complying to a language of design (Stiny 1980). Such a system will enable to deliver design solutions with quality (Eloy et al. n.d.) and at affordable prices improving satisfaction of clients and their quality of living. The system encodes knowledge on housing design principles (sizes of rooms, types of rooms and there preferable connections) as well as in the construction techniques that underlies the shape composition principles.